Can dog-assisted and relaxation interventions boost spatial ability in children with and without special educational needs? A longitudinal, randomized controlled trial - Brelsford, Victoria L.; Dimolareva, Mirena; Rowan, Elise; Gee, Nancy R.; Meints, Kerstin (Frontiers in Pediatrics, 2022)
Children’s spatial cognition abilities are a vital part of their learning and cognitive development, and important for their problem-solving capabilities, the development of mathematical skills and progress in Science, Technology, Engineering and Maths (STEM) topics. As many children have difficulties with STEM topic areas, and as these have suffered a decline in uptake in students, it is worthwhile to find out how performance can be enhanced at an early age. The current study is the first to investigate if dog-assisted and relaxation interventions can improve spatial abilities in school children. It makes a novel contribution to empirical research by measuring longitudinally if an Animal-Assisted Intervention (AAI) or relaxation intervention can boost children’s development of spatial abilities. Randomised controlled trials were employed over time including dog intervention, relaxation intervention and no treatment control groups. Interventions took place over 4 weeks, twice/week for 20 minutes. Children were tested in mainstream schools (N=105) and in special educational needs (SEN) schools (=64) before and after interventions, after 6 weeks, 6 months and 1 year. To assess intervention type and provide advice for subsequent best practice recommendations, dog-assisted interventions were run as individual or small group interventions. Overall, children’s spatial abilities improved over the year. Typically developing children showed higher scores and more continuous learning overall compared to children with SEN. In Study 1, children in the dog intervention group showed higher spatial ability scores immediately after interventions and after a further 6 weeks (short-term). Children in the relaxation group also showed improved scores short-term after relaxation intervention. In contrast, the no treatment control group did not improve significantly. No long-term intervention effects were observed. Interestingly, no gender differences could be observed in mainstream school children’s spatial skills. In study 2, children with SEN saw immediate improvements in spatial abilities after relaxation intervention sessions. No changes were seen after dog interventions or in the no treatment control group. Participants’ pet ownership status had no effect in either cohort. These are the first findings showing that AAI and relaxation interventions benefit children’s spatial abilities in varied educational settings and help children achieve their learning potential.